2006
DOI: 10.1108/01437720610683976
|View full text |Cite
|
Sign up to set email alerts
|

Constructing factors related to worker retention

Abstract: PurposeThe purpose of this paper is to examine the effect of individual‐based, firm‐based, and market factors on job retention, basing its hypotheses on human capital theory and signaling models.Design/methodology/approachBy collecting secondary data on 180 employees who left their jobs at one firm and interviewing human resource managers and those who left for other jobs, factors determining the decision to stay with a firm for a certain period were investigated. Hierarchical regression analyses were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 71 publications
7
58
0
4
Order By: Relevance
“…In the recent time, Bairi, Manohar & Kundu (2011) have acknowledged that employee retention has emerged as the focus point of many researches in the field of HRM, particularly as part of talent management programs in which many of the human resources practitioners have integrated into the program (Law, 2003;Gallagher et al 2006). On the contrary, Huang, Lin, & Chuang (2006) in their studies have observed that despite the emerging importance of employee retention, only few studies have examined the concept. Furthermore, Huang et al (2006) argued that most existing studies tend to focus more on turnover than on retention, itself.…”
Section: Hrm Outcome (Employee Retention)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent time, Bairi, Manohar & Kundu (2011) have acknowledged that employee retention has emerged as the focus point of many researches in the field of HRM, particularly as part of talent management programs in which many of the human resources practitioners have integrated into the program (Law, 2003;Gallagher et al 2006). On the contrary, Huang, Lin, & Chuang (2006) in their studies have observed that despite the emerging importance of employee retention, only few studies have examined the concept. Furthermore, Huang et al (2006) argued that most existing studies tend to focus more on turnover than on retention, itself.…”
Section: Hrm Outcome (Employee Retention)mentioning
confidence: 99%
“…On the contrary, Huang, Lin, & Chuang (2006) in their studies have observed that despite the emerging importance of employee retention, only few studies have examined the concept. Furthermore, Huang et al (2006) argued that most existing studies tend to focus more on turnover than on retention, itself.…”
Section: Hrm Outcome (Employee Retention)mentioning
confidence: 99%
“…Previos studies have identified age, gender, occupation and industry to correlate with organizational commitment and intention to stay (Huang et al, 2006;Pare and Tremblay, 2007;Taplin and Winterton, 2007). The four control variables were coded as follows: age (1 = 20-29 years, 2 = 30-39 years, 3 = 40-49 years, 4 = 50 years or older), gender (1 = male, 2 = female), occupation (1 = administrator, 2 = information technology technician, 3 = manager, 4 = librarian, 5 = faculty member, 6 = accountant, 7 = engineer, 8 = HR personnel, 9 = physician, 10 = researcher, 11 = nurse, 12 = veterinary personnel, 13 = navy officer, 14 = navy personnel), and industry (1 = university sector, 2 = health care sector, 3 = public sector, 4 = private sector).…”
Section: Control Variablesmentioning
confidence: 99%
“…These factors include future wages, marriage status, geographic location, age, education, race, and time at sea (Warner & Goldberg, 1984;Brown, 1985;Schiller et al, 1991;Rosen, 1992;Asch & Warner, 2001;Carrell & West, 2005;Huang et al, 2006). The likelihood of earning more money by leaving the military is a key determinant in any retention decision.…”
Section: Retention Modelsmentioning
confidence: 99%